Adoption of Science Programs--Another Look. - Bredderman, Ted (Elementary School Journal, 1977)
The article focuses on nationally-supported improvement programs aimed at the curriculum for elementary school science. The Elementary Science Study, Science—A Process Approach and the Science Curriculum Improvement Study programs in particular have been adopted by schools. Evidence revealed that children involved in such programs show higher-level thinking processes and problem-solving skills.